SIKAP MASYARAKAT TERHADAP PENETAPAN AREAL KERJA HUTAN DESA DI DESA NANGA BETUNG KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU - Abidin, Syamsul; Muin, Sudirman; Oramahi, H.A. (Universitas Tanjungpura, 2016)
In this research, which led to the positive people’s atittude tovillage forest of working area designation is the high level of public knowledge about the forest villages so that they know and understand about the function and benefits of village forest. this is evidenced at the time of the study, the villagers nanga betung very cooperative and willing to be invited discussion on the village forest. People who have a view or a good opinion of the importance of the activities of village forest will be positive perception about the functions and benefits of forest villages, public perception of the policy village forest of working area designation and public perception of management institutional of village forest compared to people who have a perception of neutral and negative. The knowledge that they can be through outreach and facilitation of village forest, accompanied by the Forestry Service and the NGO / LSM, leaflets by relevant agencies, and other sources so that they understand about the village forest of working area designation. From the discussion to the respondents, in general perceive that management institutions of village forest which have LPHD (Lembaga Pengelola Hutan Desa). That is, unconsciously people already perceive that the village forest is managed for a purpose because there is managers of institution. They are also involved in the preparation of strategic plans in the coming 1-5 years. Respondents who answered neutral and negative that the person concerned is a citizen who is not involved in LPHD or do not feel part of LPHD. Keywords : Attitude, Perception, Village Forest, management institutions